2018
DOI: 10.1016/j.tra.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mode choice for intercity travel: Application of a hybrid choice model to two distinct US corridors

Abstract: With growing concerns about greenhouse gas emissions and traffic congestion, there is an emphasis on encouraging shifts to public transport, for both short and long distance travel. Major differences exist across countries in how successful these efforts are, and the United States is often used as the key example of a country with a strong resistance to shifting away from private car use. Even within the United States however, there is strong heterogeneity across regions and across different types of traveller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Note that the covariates of the price coefficient enter only the third term of equation ( 2) to avoid multiplication by the scale parameter (see Hess and Train 2017). Following Hess et al (2018), we directly estimated the income elasticity and price elasticity ℎ . However, not all respondents stated their income, which was accounted for by a dummy variable .…”
Section: ~( ²mentioning
confidence: 99%
“…Note that the covariates of the price coefficient enter only the third term of equation ( 2) to avoid multiplication by the scale parameter (see Hess and Train 2017). Following Hess et al (2018), we directly estimated the income elasticity and price elasticity ℎ . However, not all respondents stated their income, which was accounted for by a dummy variable .…”
Section: ~( ²mentioning
confidence: 99%
“…Previous studies have shown that intercity travel mode choice is affected by sociodemographic factors, including gender [10,12,13], age [12,13,31], occupation [12], income [10,13,32,33], and car ownership [13]. Martín et al [34] found that males are more likely to use public transport than females.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Equation (18), (19) and (20) can be combined to yield the joint unconditional probability distribution function for the choice and indicators as follows: Equation 21…”
Section: Parameter Estimationmentioning
confidence: 99%